2012
DOI: 10.2166/wst.2012.299
|View full text |Cite
|
Sign up to set email alerts
|

Study on the removal efficiency of UF membranes using bacteriophages in bench-scale and semi-technical scale

Abstract: To determine the removal efficiency of ultrafiltration (UF) membranes for nano-particles in the size range of viruses the state of the art uses challenge tests with virus-spiked water. This work focuses on bench-scale and semi-technical scale experiments. Different experimental parameters influencing the removal efficiency of the tested UF membrane modules were analyzed and evaluated for bench- and semi-technical scale experiments. Organic matter in the water matrix highly influenced the removal of the tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…A few previous studies have shown an increase of bacteriophage retention with increasing organic contents in the feed water (Huang et al, 2012;Kreißel et al, 2012). The enhancement of bacteriophage removal was mainly attributed to (1) the accumulated fouling layers on the membranes due to rejected large-sized organics (similar to a 'dynamic membrane'), and (2) the greater pore constriction by the small organics that adhered to the membrane matrix.…”
Section: Effect Of Operating Conditions On Bacteriophage Removal Effi...mentioning
confidence: 94%
See 4 more Smart Citations
“…A few previous studies have shown an increase of bacteriophage retention with increasing organic contents in the feed water (Huang et al, 2012;Kreißel et al, 2012). The enhancement of bacteriophage removal was mainly attributed to (1) the accumulated fouling layers on the membranes due to rejected large-sized organics (similar to a 'dynamic membrane'), and (2) the greater pore constriction by the small organics that adhered to the membrane matrix.…”
Section: Effect Of Operating Conditions On Bacteriophage Removal Effi...mentioning
confidence: 94%
“…Although all reported model bacteriophages have negatively-charged surfaces at neutral pH condition, their hydrophobic nature and isoelectric points are different (e.g., isoelectric point is 3.1 for MS2, 2.1 for GA, 2.7 for Qβ, and 2.1 for SP (Langlet et al, 2008); 3.8 to 5.5 for B-14 (Purnell et al, 2015)). The surface properties of bacteriophages determine their aggregation tendency, adsorption by natural organic compounds/sludge flocs, and interaction with membrane surfaces, which impact bacteriophage removal efficiency in natural waters and wastewaters (Boudaud et al, 2012;Chaudhry et al, 2015a;ElHadidy et al, 2013ElHadidy et al, , 2014Kreißel et al, 2012). For example, in natural waters, the bacteriophages with greater hydrophobicity are more efficiently rejected by membranes possibly due to their stronger interaction with natural organic substances and membrane surface (Boudaud et al, 2012;Kreißel et al, 2012).…”
Section: The Factors That Influencing Bacteriophage Removal In Membra...mentioning
confidence: 99%
See 3 more Smart Citations